Malignancy in Renal Transplant Recipients - Ergün Parmaksız; Meral Meşe; Serkan Feyyaz Yalın; Ali Burak Haras; Okan Akyüz; Zerrin Bicik Bahçabaşı (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]The types of post-transplantation malignancies may vary among different geographic regions and ethnic populations. The aim of the present study was to determine the risk and incidence of de novo carcinomas, clinical characteristics, and outcomes in renal transplant recipients (RTRs) who are followed up in our center and if there is an accumulation of one type of malignity and to examine screening procedures and frequency.